Pensando na Paz na América do Sul. Aspectos da violência estrutural nos casos do Brasil, Argentina, Chile e Venezuela - Winand, Érica; Guerra Silvestre, Cristiano; Rodrigues, Jorge (Hemisferio - Revista del Colegio Interamericano de Defensa, 2017)
This article’s objective is to explore, in a panoramic perspective, obstacles imposed to the so-called “positive peace” in South-American countries, in light of determining and conditioning factors. Starting with criteria connected to the intersection of strictly economic data — and others related to human development — we chose Brazil, Argentina, Chile and Venezuela for a special analysis, comparing the most important aspects regarding the situation of structural violence in each case, as well as the existence of policies strengthening fertile environments in order to establish a positive relationship between human development and peace